Adaptasi Pendidikan Formal Berbasis Pesantren Terhadap Perkembangan Teknologi dalam Menjaga Nilai-Nilai Moral Pesantren: Studi di MI Nurul Huda Surabaya - Ahmad Syifa'ul Fatoni; Fatchur Rochman; Muhammat Tri Yudha Al Hidayat; Mokhamad Arfangga Akhbar; Syaidatul Khumairoh; M. Amir; M. Rondhi (IIQ An Nur Yogyakarta, 2026)
The rapid development of digital technology has transformed Islamic education while posing challenges to preserving the moral values that characterize pesantren-based education. Consequently, formal educational institutions rooted in the pesantren tradition are required to adapt to technological advancements without losing their educational identity and moral foundations. This study aims to analyze how a pesantren-based formal educational institution adapts to technological development while maintaining pesantren moral values at MI Nurul Huda Sambisari Surabaya. This research employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation involving the principal, teachers, and students. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure data validity. The findings reveal that technological adaptation is implemented by integrating digital media into the learning process while reinforcing pesantren moral values, including exemplary conduct (uswah hasanah), adab (proper conduct), religious habituation, discipline, and responsibility. Rather than being perceived as a threat, technology is utilized as an educational medium through the strengthening of Islamic digital literacy and pesantren educational culture. The study also finds that students' behavioral changes in using digital technology are an implication of the continuous internalization of moral values within the school environment. This study concludes that pesantren-based formal education demonstrates strong adaptive capacity in responding to digital transformation while preserving moral values as the foundation of Islamic education.